Voltage controlled ring oscillator for RF Applications in 0.18μm CMOS Technology / Mohammad Arif Sobhan Bhuiyan...[et al.] - Sobhan Bhuiyan, Mohammad Arif; Nordin, Zainal Abidin; Ibne Reaz, Mamun (2014)
A compact and power efficient high performance Voltage Controlled Oscillator (VCO) is a must in analog and digital circuits especially in the communication system. But the best trade-off among the performance parameters is a challenge for researchers. In this paper, a design of a compact 3-stage differential voltage controlled ring oscillator (VCRO) with low phase noise, low power and higher tuning bandwidth is proposed in 0.18μm CMOS technology. The VCRO is designed with symmetric load and positive feedback techniques to achieve higher gain and minimum delay. The proposed VCRO can operate at tuning range of 3.9-5.0 GHz at 1.6V supply voltage. The circuit consumes only 1.0757 mW of power and produces -129dbc/Hz. The total active area of the proposed VCRO is only (11.74 x 37.73) μm2. Such a VCO can be the best choice for compact and low-power RF applications.